2014
DOI: 10.1002/mus.24245
|View full text |Cite
|
Sign up to set email alerts
|

Small‐fiber neuropathy with cardiac denervation in postural tachycardia syndrome

Abstract: A subset of neuropathic POTS patients may harbor mild small fiber neuropathy with abnormalities of unmyelinated nerve fibers in the skin associated with reduced myocardial postganglionic sympathetic innervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 48 publications
2
22
0
3
Order By: Relevance
“…Our patient has abnormal sudomotor function and complaints of anhidrosis, suggesting abnormal sympathetic post-ganglionic activity. In addition, the presence of orthostatic tachycardia suggests dysfunction of the small fiber sympathetic nervous system [20]. Altogether the presentation of pain in the distal extremities with abnormal post-ganglionic sympathetic activity suggests that small, unmyelinated nerve fibers are dysfunctional in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient has abnormal sudomotor function and complaints of anhidrosis, suggesting abnormal sympathetic post-ganglionic activity. In addition, the presence of orthostatic tachycardia suggests dysfunction of the small fiber sympathetic nervous system [20]. Altogether the presentation of pain in the distal extremities with abnormal post-ganglionic sympathetic activity suggests that small, unmyelinated nerve fibers are dysfunctional in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced myocardial meta-iodobenzylguanidine uptake indicating reduced cardiac sympathetic neuronal uptake function has been reported in 20% of patients with POTS, suggesting that cardiac sympathetic denervation may be present in this condition (Haensch et al, 2010). More recently it was also demonstrated that reduced myocardial meta-iodobenzylguanidine uptake correlated with the density of sympathetic and somatic C-fiber innervation measured from skin biopsies and suggested that loss of distal sympathetic innervation may produce an exaggerated sympathetic response in innervated tissues such as the heart, resulting in tachycardia (Haensch et al, 2014). …”
Section: Sympathetic Denervation May Be Associated With Potsmentioning
confidence: 99%
“…However, these figures do not fully capture patients with small-fiber polyneuropathy (SFPN), although it is the most common presentation of distal polyneuropathy. Multiple labs now report evidence of SFPN in about 40% of patients with fibromyalgia [11, 21, 26]. Since fibromyalgia affects 2-5% of the world’s population [17, 28], SFPN may affect millions.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular, gastrointestinal, microvascular and/or sweating symptoms can reflect either autonomic or somatic axonopathy since many internal organs and tissues have dual small-fiber innervation [1]. Neurogenic dysregulation of the microvessels alone causes a wide array of symptoms including postural orthostatic tachycardia syndrome [11] fatigue, and even cognitive dysfunction [22]. …”
Section: Introductionmentioning
confidence: 99%